Metabolic response during intermittent graded sprint running in moderate hypobaric hypoxia in competitive middle-distance runners - Ogawa, T.; Hayashi, K.; Ichinose, M.; Wada, H.; Nishiyasu, T. (European Journal of Applied Physiology, 2007)
The purpose of this study was to determine whether the metabolic response and running performance during intermittent graded sprint running were affected by moderate hypobaric hypoxia (H; 2,500 m above sea level) in competitive middle-distance runners. Nine male runners performed intermittent graded sprint running until exhaustion, to evaluate the metabolic response and running performance in H and normobaric normoxia (N). The test constructed of incremental (25 m min-1) 20 s running bouts (4° inclination) interspaced with 100 s recovery periods. Maximal running speed was not different between conditions [453 (7) m min-1 vs. 458 (4) m min-1 in N vs. H]. V\textO2VO2 at each speed was lower in H than N (ANOVA; P < 0.05). Although, oxygen deficit (D\textO2 )DO2 at each speed was not different between N and H (ANOVA; P = 0.1), total accumulated D\textO2DO2 in all bouts was significantly higher in H than N [165 (10) ml kg-1 in N and 173 (10) ml kg-1 in H]. The ratio of D\textO2·V\textO2-1DO2VO2-1 was similar in all bouts, but higher in H than N. These results suggest that intermittent graded sprint running performance is not affected by moderate hypobaria despite a reduction in the energy supplied by aerobic metabolism due to a compensatory increase in the energy supplied by the anaerobic metabolism in competitive middle-distance runners.